Case study in which the Deutsch-Jozsa algorithm responds with pure states - Marinho, Eraldo P. [UNESP] (IOP Publishing, 2019)
A theoretical essay is presented on a particular type of balanced functions that allow the Deutsch-Jozsa algorithm to produce pure state instead of mixed states. Such results occur if and only if the balanced functions are linear combinations (modulo 2) of a set of balanced clock functions, that is, clock functions with periods that are power of 2.